Assessing Consequences of Intraaortic Balloon Counterpulsation Versus Left Ventricular Assist Devices at the Time of Heart Transplantation. Issue 3 (May 2016) - Castleberry, Anthony W.; DeVore, Adam D.; Southerland, Kevin W.; Meza, James M.; Irish, William D.; Rogers, Joseph G.; Milano, Carmelo A.; Patel, Chetan B.
Abstract : The proportion of heart transplant recipients bridged with durable, intracorporeal left ventricular assist devices (dLVADs) has dramatically increased; however, concern exists regarding obligate repeat sternotomy, increased bleeding risk because of anticoagulation and acquired von Willebrand disease, and increased rates of allosensitization. Whether dLVAD patients have impaired posttransplant outcomes compared with equivalent patients with less invasive intraaortic balloon pump counterpulsation (IABP) at the time of transplant is unknown. Therefore, we analyzed adult, first time, heart-only transplant procedures with dLVAD (n = 2, 636) compared with IABP (n = 571) at the time of transplant based on data from the United Network for Organ Sharing (UNOS) July 2004 to December 2011. There was clear geographic variation in IABP and dLVAD at transplant. Multivariable analysis demonstrated equivalent cumulative risk of death (adjusted Cox proportional hazard ratio, 1.08; 95% confidence interval, 0.87–1.33; p = 0.51). There was no significant difference in adjusted comparison of perioperative morality, length of stay, postoperative renal failure requiring dialysis, or early acute rejection ( p ≥ 0.14 for all). Therefore, data from UNOS suggest that the presence of dLVAD at the time of heart transplantation does not have a detrimental effect on postoperative outcomes compared with IABP, which must be considered in the context of pretransplant mortality and locoregional organ availability. Abstract : Supplemental Digital Content is available in the text.